Coronary Revascularization in Patients With Stable Coronary Artery Disease: The Role of Imaging - Neglia, Danilo; Maroz-Vadalazhskaya, Natallia; Carrabba, Nazario; Liga, Riccardo (Frontiers in Cardiovascular Medicine, 2021)
Abstract In the last decades, the effective management of some cardiovascular risk factors in the general population has led to a progressive decrease in the prevalence of coronary artery disease (CAD). Nevertheless, coronary heart disease remains the major cause of death in developed and developing countries and chronic coronary syndromes (CCS) are still a major target of utilization of non-invasive cardiac imaging and invasive procedures. Current guidelines recommend the use of non-invasive imaging in patients with CCS to identify subjects at higher risk to be referred for invasive coronary angiography and possible revascularization. These recommendations are challenged by two opposite lines of evidence. Recent trials have somewhat questioned the efficacy of coronary revascularization as compared with optimal medical therapy in CCS. As a consequence the role of imaging in these patients and in in patients with ischemic cardiomyopathy is under debate. On the other hand, real-life data indicate that a consistent proportion of patients undergo invasive procedure and are revascularizaed without any previous non-invasive imaging characterization. On top of this, the impact of COVID-19 pandemic on the sanitary systems caused a change in the current management of patients with CAD. In the present review we will discuss these conflicting data analysing the evidence which has been recently accumulated as well as the gaps of knowledge which should still be filled.